The effect of training program using strength training and small sided-games on the development of explosive strength and the ability to recover between repeated sprint in - Khalif Abdul Qadir; Mazari fatah (sports creativity, 2025)
The aim of this study was to examine the effect of a proposed training program, trough using of small sided-games and strength training in developing of explosive strength and the ability to recover between repeated sprint in football players. The program was applied to two samples. The experimental sample consisted of 12 players (Age 18.28 ± 0.48, height 1.70 ± 0.36, body mass 57.42 ± 6.34), and the control sample consisted 12 players (age 18.57 ± 0.53, height 1.71 ± 0.04, body mass 58 ± 3.87) the measurement using of this study tow test The results showed that the small sided and strength training game had a positive effect, on the development of, explosive strength and the ability to recover between repeated sprint in significance level (P < 0.05)